Veterinary Expert Opinion on Potential Drivers and Opportunities for Changing Antimicrobial Usage Practices in Livestock in Denmark, Portugal, and Switzerland - Carmo, Luís P.; Nielsen, Liza R.; Alban, Lis; da Costa, Paulo M.; Schüpbach-Regula, Gertraud; Magouras, Ioannis (Frontiers in Veterinary Science, 2018)
Reducing antimicrobial use (AMU) in livestock is requested by Public Health authorities. Ideally, this should be achieved without jeopardizing production output or animal health and welfare. Thus, efficient measures must be identified and developed to target drivers of AMU. Veterinarians play a central role in the identification and implementation of such efficient interventions. Sixty-seven veterinarians with expertise in livestock production in Denmark, Portugal, and Switzerland participated in an expert opinion study aimed at investigating experiences and opinions of veterinarians about the driving forces and practices related to AMU in the main livestock sectors (broiler, dairy cattle, fattening/veal calf, and pig industry) of the aforementioned countries. Opinions on potential factors influencing the choice of antimicrobials and opportunities to reduce AMU were collected. Antibiograms are seldom used, mainly due to the time lag between testing and obtaining the results. The perceived percentage of treatment failures varied between countries and livestock sectors; however, little changes were reported over time (2005−2015). The animal health problems of each livestock sector most frequently leading to AMU did not vary substantially between countries. Mandatory official interventions (i.e., binding measures applied by national or international authorities) were highlighted as having the biggest impact on AMU. There was a variation in the experts’ opinion regarding feasibility and impact of interventions both between countries and livestock sectors. Nevertheless, improved biosecurity and education of veterinarians frequently received high scores. Most veterinarians believed that AMU can be reduced. The median potential reduction estimates varied from 1% in Swiss broilers to 50% in Portuguese broilers and veal/fattening calves in all countries. We hypothesize that the differences in views could be related to disease epidemiology, animal husbandry, and socio-economic factors. A profound investigation of these disparities would provide the required knowledge for developing targeted strategies to tackle AMU and consequently resistance development. However, experts also agreed that mandatory official interventions could have the greatest impact on antimicrobial consumption. Furthermore, improvement of biosecurity and education of veterinarians, the use of zinc oxide (in pigs), improving vaccination strategies, and the creation of treatment plans were the measures considered to have the largest potential to reduce AMU. This paper can inform policymakers in Europe and countries with a similar animal production regarding their AMU policy.